Does Experiential Avoidance Explain the Relationships between Shame, PTSD Symptoms, and Compulsive Sexual Behavior among Women in Substance Use Treatment? - Brem, Meagan J. (Clin Psychol Psychother, 2018)
OBJECTIVE: Untreated compulsive sexual behavior (CSB) poses a risk to efficacious substance use disorder (SUD) treatment. Yet, the ways in which CSB manifests in women with SUDs remains poorly understood. Shame and trauma exposure are well-documented correlates for women’s CSB. Prior theory suggested women with shame and trauma-related symptoms may engage in CSB in an effort to escape aversive internal experiences. Thus, the present study examined experiential avoidance as a mediator of the relationship between defectiveness/shame beliefs, post-traumatic stress disorder (PTSD) symptoms, and CSB in a sample of women with SUDs. METHOD: Cross-sectional, self-report data were collected from 446 women (M age = 37.40) in residential treatment for SUDs. RESULTS: Experiential avoidance partially mediated the relationship between both PTSD symptoms and defectiveness/shame beliefs and CSB. CONCLUSIONS: These results extend theoretical conceptualizations of women’s CSB to a treatment population. CSB intervention efforts may benefit from targeting women’s avoidance of painful experiences.